Biology and influence of Pterotylenchus cecidogenus on Desmodium ovalifolium - Stanton, J.M. (1986)
Pterotylenchus cecidogenus did not inhibit germination of Desmodium ovalifolium but did reduce survival of seedlings and root and stem growth. Stem gall formation was associated with nematode population densities which were positively correlated with plant age at time of inoculation. Nematode population densities increased 100 times in 52 days following inoculation.